Contingency Plan For Managing Slope-Related Risks A Case Study For Menora Tunnel In Malaysia - Abdullah, Siti Najwa
Nowadays, the world is witnessing an ever-increasing need for tunnels because of their unique characteristics and potential applications. However, tunnel is facing many problems and risks such as safety, stability and environmental influence in excavation and operation. Around the world, there have been serious failures in tunnel during operation and maintenance stage and these cases have resulted in fatalities, damage to property and other socio-economic consequences. The aim of this study is to identify the potential slope-related risks and determine their risk ranking according to their priority importance towards successful delivery of tunnelling projects. The selected case study tunnelling project is Menora Tunnel which is located at Jelapang, Perak. Throughout the study, the significant risks are identified and then ranked via the Analytic Hierarchy Process (AHP) pairwise comparison, which analyses the criticality and importance of each risk. Most of these risks are identified, quantified, minimized and prioritized to minimize the consequences and their impact on certain projects. There are total five slope-related risks have been identified. Amongst them, slope failure has the greatest importance due to the event of sudden collapse of the slope, there are potential impacts on highway tunnel users, thus resulting towards a higher fatality rate. Heavy rainfall will affect the condition and reduce the strength of soil near to the tunnel. Therefore, a risk contingency plan is needed to lessen the damage of all these risks when they occur. Contingency plan is playing an important role as an adequate preparation in order to make sure the planning will be respond quickly and effectively to a crisis situation when it occurs. Without the plan in place, the full impact of the risk could greatly affect the operation and maintenance of tunnel.